PENERAPAN MODEL PEMBELAJARAN EXPERIENTIAL LEARNING DALAM MENINGKATKAN HASIL BELAJAR PADA POKOK BAHASAN SUGGESTIONS AND OFFERS - AAN SAJIATMOJO (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2022)
Based on the description of the research results that have been presented, the researcher draws conclusions from the results of research conducted at SMA Negeri 2 Tanjung Selor, namely that there is an increase in the learning outcomes of class XI IPA students at SMA Negeri 2 Tanjung Selor in the Subject of Suggestions and offers. In the pre-cycle 7 students who studied thoroughly, then increased in cycle 1 there were 21 students who completed learning and in cycle 2 reached 29 students. The percentage of student completeness shows in the pre-cycle 22.2%, then increases to 66.6% in cycle 1 and becomes 94.4% in cycle 2. Then research with the problem